1967
DOI: 10.2135/cropsci1967.0011183x000700040021x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Saponin of Several Alfalfa Varieties Using Chemical and Biochemical Assays1

Abstract: Saponin content of alfalfa (Medicago sativa L.) was affected by variety, stage of growth, and percentage of leaves. Leaves were higher in saponin content than stems and immature growth was higher in saponin content than more mature growth. The ‘Du Puits’ variety was higher in saponin content than ‘Lahontan’ and this difference became greater as the growing season progressed. The varietal difference was reflected in the growth rate of chicks fed alfalfa meal differing in saponin content and in the growth rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Poultry are more sensitive than other farm animals. A variety of alfalfa with 1.47% of saponins caused an average reduction of 11% in weight gain of chicks compared to a lowsaponin variety containing 0.59% of the active compounds [142,143]. No effects were reported when calves were fed with alfalfa hay containing up to 2.62% saponin [144].…”
Section: Effects On Animalsmentioning
confidence: 95%
“…Poultry are more sensitive than other farm animals. A variety of alfalfa with 1.47% of saponins caused an average reduction of 11% in weight gain of chicks compared to a lowsaponin variety containing 0.59% of the active compounds [142,143]. No effects were reported when calves were fed with alfalfa hay containing up to 2.62% saponin [144].…”
Section: Effects On Animalsmentioning
confidence: 95%
“…Alfalfa leaves and younger vegetative growth were found to have a higher saponin content compared with stems and more mature growth [ 96 ]. Saponins form a stable froth when shaken in water.…”
Section: Alfalfa and Pasture Bloatmentioning
confidence: 99%
“…These findings suggest that saponins might be involved in some cases of frothy bloat, but they are not required for the formation of stable foam in the rumen. Saponin content, ratio between sapogenins and sapogenin structure differ among alfalfa cultivars and might determine the propensity to develop pasture bloat [ 96 , 104 , 105 ]. Little is known about the effect of environment, season, climatic conditions and growth conditions on saponin content, the ratio between individual sapogenins and on sapogenin structure in alfalfa [ 105 ].…”
Section: Alfalfa and Pasture Bloatmentioning
confidence: 99%
“…Detailed studies with alfalfa, have shown that content and compositional profile of saponins is influenced by several factors such as environment, genotype, physiological stage of growth, and plant part (Pedersen et al 1967;Pedersen and Wang 1971;Berrang et al 1974;Quazi 1975;Tava et al 1993Tava et al , 1999Tava and Pecetti 1998;Pecetti et al 2006). Saponins from M. sativa aerial parts (tops) are characterized by high amounts of medicagenic acid glycosides (40-60%), followed by zanhic acid (10-25%), hederagenin (2-8%), bayogenin (3-7%) and soyasapogenol (10-20%) glycosides.…”
Section: Chemical Profile Of Saponins In M Sativamentioning
confidence: 99%